THE EFFECTIVENESS OF LOCAL WISDOM-BASED ELECTRONIC LKPD TO IMPROVE LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Latifah, Ulfatul Laili Nur; Sulistyorini, Sri; Sumarti, Sri Susilogati (Universitas Pendidikan Indonesia, 2024)
The purpose of this research is to test the effectiveness of Electronic LKPD of local wisdom-based that were valid, practical, and effective to improve student learning outcomes, especially in science subjects in elementary school. The research design used is Research and Development (RD) design, the procedure or stage of developing local wisdom-based Electronic LKPD used a development research procedure consisting of eight stages starting from finding potential and problems, until the report preparation stage. The average in the control group was 69.96, while the average of the experimental class was 83.31. The t-test results gained a Sig. value of 0.028 0.05, it concluded that there was a significant difference between the average student learning outcomes of the control group and the experimental group. The N-Gain test results also show that the average N-Gain value for the control class is 25.1%, while the average N-Gain value for the experimental class is 58.3%. These results proved that electronic LKPDs based on local wisdom are effective as learning media to improve student learning outcomes. Electronic LKPDs based on local wisdom as teaching materials for learning Natural Sciences are more effective in improving student learning outcomes. Learning by using Electronic LKPD of local wisdom-based as a medium for learning Natural Sciences was more effective, which is indicated by the increase in student learning outcomes both cognitive and psychomotor. Learning by using Electronic LKPD based on local wisdom as a medium for learning Natural Sciences contributes to better student learning outcomes because with Electronic LKPD of local wisdom-based learning becomes effective, students were more interested and enthusiastic in learning. The conclusion of this research is that Electronic LKPD of local wisdom-based was effective as a learning media to improve student learning outcomes.